THE INFLUENCE OF HERMENEUTICS IN DOUBLE MOVEMENT THEORY (CRITICAL ANALYSIS OF FAZLURRAHMAN'S INTERPRETATION METHODOLOGY) - Nugroho, Kharis; Kiram, Muhammad Zawil; Andriawan, Didik (QiST: Journal of Quran and Tafseer Studies, 2023)
This study aims to trace the influence of hermeneutics in the theory of double movement. This theory is a new interpretive methodology initiated by Fazlurrahman in response to modernization. In addition, dissatisfaction with the methodology of classical scholarly exegesis is also the reason for this idea. After tracing this theory, it is found that there are several hermeneutic schools behind this theory. Therefore, in the implementation of the double movement theory, controversial legal products are often produced considering that in hermeneutics there is no definite law. While in Islam there are rules that are definite and cannot change the law. With this critical analysis-style research, it is hoped that we can understand and assess the effectiveness of the double movement theory in the treasures of contemporary interpretation.